Uterine Fibroids (Leiomyomata) and Heavy Menstrual Bleeding - Uimari, Outi; Subramaniam, Kavita S.; Vollenhoven, Beverley; Tapmeier, Thomas T. (Frontiers in Reproductive Health, 2022)
Uterine Fibroids, or leiomyomata, affect millions of women world-wide, with a high incidence of 75% within women of reproductive age. In ~30% of patients, uterine fibroids cause menorrhagia, or heavy menstrual bleeding, and more than half of the patients experience symptoms such as heavy menstrual bleeding, pelvic pain, or infertility. Treatment is symptomatic with limited options including hysterectomy as the most radical solution. The genetic foundations of uterine fibroid growth have been traced to somatic driver mutations (MED12, HMGA2, FH−/−, and COL4A5-A6). These also lead to downstream expression of angiogenic factors including IGF-1 and IGF-2, as opposed to the VEGF-driven mechanism found in the angiogenesis of hypoxic tumors. The resulting vasculature supplying the fibroid with nutrients and oxygen is highly irregular. Of particular interest is the formation of a pseudocapsule around intramural fibroids, a unique structure within tumor angiogenesis. These aberrations in vascular architecture and network could explain the heavy menstrual bleeding observed. However, other theories have been proposed such as venous trunks, or venous lakes caused by the blocking of normal blood flow by uterine fibroids, or the increased local action of vasoactive growth factors. Here, we review and discuss the evidence for the various hypotheses proposed.